2008
DOI: 10.1179/174367508x297830
|View full text |Cite
|
Sign up to set email alerts
|

Net shaping nanopowders with powerful ultrasonic action and methods of density distribution control

Abstract: Two methods of compacting dry poly-and nanodisperse powders into compacts of a complicated shape with uniform density distribution in the volume have been developed: pressing under powerful ultrasonic action and collector pressing by the control of friction forces redistribution. Experimental measuring and simulation of the process of deformation of a powder body by different methods show that in the case of ultrasonic pressing, the dispersion of the density distribution has decreased by 20%, and the relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…There are two methods to eliminate or reduce die wall friction forces for dry powder pressing process which allow pressing into complex shape compacts, with uniform density distribution in the bulk: pressing under a powerful ultrasonic action pressing and the collector pressing [10][11][12][13][14]. The former research presented density distribution for two dimensions, but this research shown density distribution of green compact in three dimensions of cross section to angle 150 degrees as show in figure 3-5.…”
Section: Comparison Of Results Of Density Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are two methods to eliminate or reduce die wall friction forces for dry powder pressing process which allow pressing into complex shape compacts, with uniform density distribution in the bulk: pressing under a powerful ultrasonic action pressing and the collector pressing [10][11][12][13][14]. The former research presented density distribution for two dimensions, but this research shown density distribution of green compact in three dimensions of cross section to angle 150 degrees as show in figure 3-5.…”
Section: Comparison Of Results Of Density Distributionmentioning
confidence: 99%
“…The new die of conventional pressing is developed and patented by E.S. Dvilis and his group [10][11][12][13][14]. A collector pressing is a new die pressing that is called "Collector die" to make the green compact goes higher and uniform density in the volume.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, ultrasonic have been used to obtain better dispersion of a range of nanomaterials including CNTs [15][16][17]. Besides that, ultrasonic also emerged as the potential technique in material research and processing [18][19][20]. Khasanov and Dvilis [20] have showed that the better density and green strength of ZrO2-Y2O3 nanoparticles were obtained by the application of ultrasonic on the compaction step.…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, ultrasonic also emerged as the potential technique in material research and processing [18][19][20]. Khasanov and Dvilis [20] have showed that the better density and green strength of ZrO2-Y2O3 nanoparticles were obtained by the application of ultrasonic on the compaction step. Considering the promising of ultrasonic, in this research, CuCNTs composites were produced by powder metallurgy, in which the technical ultrasonic had been used to assist in the compaction step.…”
Section: Introductionmentioning
confidence: 99%